2012
DOI: 10.1097/bth.0b013e31824b9ab0
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Kirschner-wire Fixation in Distal Radius Fractures

Abstract: Distal radius and ulna fractures are the most common fractures seen in England, occurring at a rate of 22/10,000 person years. Kirschner (K)-wire fixation is a well-accepted method of treating these fractures. There is a surprising paucity of evidence on the subject of prophylactic antibiotics and the duration of K wires can be left in, as these relate to infection rates. We therefore present the results of our protocol for distal radius K-wire fixation for which: no antibiotic prophylaxis was given; we used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 18 publications
2
26
0
2
Order By: Relevance
“…However, they have showed 2% infection rate in their study. [33] In the present study, Grip strength was minimally higher in Group I compared to Group II, but this was not statistically significant as previously reported in other studies. [22,24,25] A meta-analysis study has demonstrated that external fixation may lead to greater recovery of grip strength, especially compared to fixation with locking volar plates.…”
Section: Günay Et Al Two Different Treatment Technique In Distal Radsupporting
confidence: 31%
“…However, they have showed 2% infection rate in their study. [33] In the present study, Grip strength was minimally higher in Group I compared to Group II, but this was not statistically significant as previously reported in other studies. [22,24,25] A meta-analysis study has demonstrated that external fixation may lead to greater recovery of grip strength, especially compared to fixation with locking volar plates.…”
Section: Günay Et Al Two Different Treatment Technique In Distal Radsupporting
confidence: 31%
“…Subramanian et al conducted a recent study on the use prophylactic antibiotics prior to k-wire fixation for a distal radius fracture, and concluded that they do not advocate the use of prophylactic antibiotics as it does not affect the rate of infection [59]. Further analysis should be done to investigate the benefits of prophylactic antibiotics in order to clarify the use of this prevention measure.…”
Section: Infectionmentioning
confidence: 99%
“…It has been debated whether prophylactic antibiotics should be used for percutaneous wiring of fractures and Subramanian et al [13] advised against it. Bratzler et al [14] agreed that prophylactic antibiotics should be used for open orthopaedic procedures where a foreign material is inserted.…”
Section: Resultsmentioning
confidence: 99%